THE EFFECT OF PRODUCT BRANDING AND ONLINE PROMOTIONAL VIDEOS ON CONSUMER PURCHASING DECISIONS IN MSMES - Gordius Ago; Rabiyatul Jasiyah; Suriadi Suriadi; Ivonne Ayesha; Henny Herawati (SEAN Institute, 2023)
The impact of product branding and online promotional video on consumer purchase decisions in micro, small, and medium-sized enterprises (MSMEs) is an integral component of the company's marketing strategy for supporting operations and increasing sales. According to studies, MSMEs who use effective product branding and digital advertising have better sales levels than those that do not. Consequently, the goal of this study is to investigate the impact of product branding and online promotional video on SME consumers' purchase decisions. The research strategy is quantitative and employs a questionnaire with a random sample of 10 MSME respondents. The results indicated that the variables of product branding (X1) and online promotional video (X2) had a substantial impact on the purchasing decisions of MSMEs with a reliability coefficient more than or equal to 0.70, therefore it is considered reliable.